2016
DOI: 10.1186/s12885-016-2369-z
|View full text |Cite
|
Sign up to set email alerts
|

Importance of hereditary and selected environmental risk factors in the etiology of inflammatory breast cancer: a case-comparison study

Abstract: BackgroundTo assess the importance of heredity in the etiology of inflammatory breast cancer (IBC), we compared IBC patients to several carefully chosen comparison groups with respect to the prevalence of first-degree family history of breast cancer.MethodsIBC cases (n = 141) were compared to non-inflammatory breast cancer cases (n = 178) ascertained through George Washington University (GWU) with respect to the prevalence of first-degree family history of breast cancer and selected environmental/lifestyle ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 46 publications
2
17
0
3
Order By: Relevance
“…Increased consumption of animal fat, lack of exercise, high body mass index (BMI) and obesity [101], alcohol intake [102] and cigarette smoking are also common risk factors [103].…”
Section: Risk Factors For Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Increased consumption of animal fat, lack of exercise, high body mass index (BMI) and obesity [101], alcohol intake [102] and cigarette smoking are also common risk factors [103].…”
Section: Risk Factors For Breast Cancermentioning
confidence: 99%
“…http://etd.uwc.ac.za/ Other widespread factors include exogenous oestrogen intake [102] after menopause like hormone replacement therapy or oral contraceptive pills [104][105][106][107][108][109]. Another risk factor is exposure to nuclear radiation especially for younger women.…”
Section: Risk Factors For Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…13 Other histologies, including mucinous carcinoma, have not previously been associated clearly with a family history of breast cancer. 9,14,15 The possibility of additional genetic contributions to breast cancer exists. 9,14,15 The possibility of additional genetic contributions to breast cancer exists.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, inflammatory breast cancer reportedly has been associated with a first-degree family history of breast cancer in some but not all studies; mutations in specific genes have not yet been identified. 9,14,15 The possibility of additional genetic contributions to breast cancer exists. Identification of excess familial clustering using the genealogical index of familiality (GIF) is a method that can be used to provide evidence that the risk of a disease is mediated by inherited genetic factors.…”
Section: Introductionmentioning
confidence: 99%